18th IEEE International Conference on Automated Software Engineering, 2003. Proceedings.
DOI: 10.1109/ase.2003.1240294
|View full text |Cite
|
Sign up to set email alerts
|

A new structural coverage criterion for dynamic detection of program invariants

Abstract: Dynamic detection of program invariants is emerging as an important research area with many challenging problems. Generating suitable test cases that support accurate detection of program invariants is crucial to the dynamic approach for invariant detection. In this paper, we propose a new structural coverage criterion called Invariant-coverage criterion for dynamic detection of program invariants. We also show how the invariant-coverage criterion can be used to improve the accuracy of dynamically detected inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 10 publications
1
33
0
Order By: Relevance
“…The test suites built with this method proved to be appropriate for dynamic contract inference techniques. Previous authors using dynamic techniques have stated that test suites produced with random-test generation are unsuitable for contract inference [10,14]. Our own experience shows otherwise in the case of programs that are already equipped with a few simple contract elements, with the goal of inferring additional, more sophisticated assertions.…”
Section: Test Suite Generationmentioning
confidence: 90%
“…The test suites built with this method proved to be appropriate for dynamic contract inference techniques. Previous authors using dynamic techniques have stated that test suites produced with random-test generation are unsuitable for contract inference [10,14]. Our own experience shows otherwise in the case of programs that are already equipped with a few simple contract elements, with the goal of inferring additional, more sophisticated assertions.…”
Section: Test Suite Generationmentioning
confidence: 90%
“…Gupta and Heidepriem propose a new structural coverage criterion called invariant-coverage criterion for dynamic detection of program invariants [18]. Their experimental results showed that invariant-coverage test suites could effectively augment branch coverage and definition-use pair coverage test suites to remove spurious inferred invariants.…”
Section: Operational-abstraction-based Testingmentioning
confidence: 99%
“…We note the existence of many active research projects on generating high-coverage test inputs and efficient test suites. In particular, we can take advantage of an entire body of work on generating test suites specifically for dynamic invariant detection [29]- [31].…”
Section: Threats To Validitymentioning
confidence: 99%